PENGARUH PROMOSI JABATAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi pada Giant Ekstra Nangka Pekanbaru) - Novita Yendri Herman; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of position promotions and compensation on employee performance partially and simultaneously. This study uses questionnaires as a means of collecting data distributed to 93 employees in Giant Ekstra Nangka Pekanbaru. The data from the questionnaire was further processed using descriptive analysis and statistical analysis using SPSS 17.0 by performing validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis (R²) and hypothesis test with t test (partial) and F ( Simultaneous).The results showed that the results of the first hypothesis testing of position promotion employee performance is(10,637) > (1,986), meaning that position promotions variables significantly affect employee performance. Both compesation on employee performance is (10,637) > (1,986), meaning compesation has a significant effect on employee performance. The result of F test of position promotions and compensation on employee performance is(76,603) >(3,100), meaning position promotions and compensation simultaneously have a significant effect on employee performance.Keywords: Position Promotion, Compensation, Employee Performance